Editorial: Critical Narrative Literacy - Michael Prusse (CLELEjournal)
The editorial for issue 13.1 discusses critical narrative literacy as an essential component of English language teaching. By means of confrontation with multiple narrative perspectives students can develop into critical readers, responsible citizens, and caretakers of the planet.